Solid γ-Cyclodextrin Inclusion Compound with Gingerols, a Multi-Component Guest: Preparation, Properties and Application in Yogurt - Joana M. Pais; Bruna Pereira; Filipe A. Almeida Paz; Susana M. Cardoso; Susana S. Braga (Biomolecules, 2020)
Gingerols from the rhizome of fresh ginger (Zingiber officinale) were obtained by a simple extraction, followed by purification. The gingerols extract was composed of 6-gingerol (54%), 8-gingerol (20%), and 10-gingerol (26%). It was included into γ-cyclodextrin by classic co-dissolution procedures. Solid-state characterisation of γ-cyclodextrin·gingerols shows that this inclusion compound features 1:1 host-to-guest stoichiometry and that it is a microcrystalline powder with a crystalline cell that belongs to the tetragonal space group 4212, having the host molecules stacked in infinite channels where the gingerols are accommodated. In chimico studies with ABTS•+ scavenging, NO• scavenging, β-carotene peroxidation, and 5-LOX inhibition show that γ-cyclodextrin is a suitable carrier for gingerols, because it does not alter their reactivity towards these substances. Yogurt was tested as a matrix for the incorporation of gingerols and γ-cyclodextrin·gingerols into foodstuff. The colour of the fortified yogurt suffered little alterations. In the case of yogurt with the inclusion compound, γ-cyclodextrin·gingerols, as fortificant, these alterations were not perceptible to the naked eye. Moreover, yogurt with γ-cyclodextrin·gingerols showed a good antioxidant activity, thus being suitable for use in nutraceutical applications.